Anaplastic Ependymoma in a Child With Sickle Cell Anemia: A Case Report Highlighting Treatment Challenges for Young Children With Central Nervous System Tumors and Underlying Vasculopathy. Issue 3 (21st October 2015) - Crotty, Erin E.; Meier, Emily R.; Wells, Elizabeth M.; Hwang, Eugene I.; Packer, Roger J.
Abstract : A 3‐year‐old boy with sickle cell anemia (SCA) presented with progressive daily emesis and was found to have an anaplastic ependymoma. Radiation therapy and chemotherapy are usually employed after subtotal resections of anaplastic ependymomas, although the benefits from chemotherapy are unclear. To mitigate the risks of adjuvant treatment in this patient at risk for SCA‐associated vasculopathy, renal impairment, and other end‐organ damage, proton beam irradiation without chemotherapy was chosen. Scheduled packed red blood cell transfusions were instituted to maintain sickle hemoglobin levels less than 30%. This case highlights treatment complexities for malignant brain tumors in patients predisposed to treatment‐related adverse effects.